Fuzzy Set Theory and Arithmetic Operations On Fuzzy N Umbers - Jayasri, P.; Elavarasi, P. (International Journal of Scientific Research and Management (IJSRM), 2018)
In this paper we represent a fuzzy set theory and arithmetic operation on fuzzy numbers. The fuzzy set theory to derived operation on fuzzy set and fuzzy arithmetic operation. The produce with operation on closed interval.